ERRORS AND DIFFICULTIES IN TRANSLATING LEGAL TEXTS - Camelia, CHIRILA (Strategii Manageriale)
Nowadays the accurate translation of legal texts has become highly important as the mistranslation of a passage in a contract, for example, could lead to lawsuits and loss of money. Consequently, the translation of legal texts to other languages faces many difficulties and only professional translators specialised in legal translation should deal with the translation of legal documents and scholarly writings. The purpose of this paper is to analyze translation from three perspectives: translation quality, errors and difficulties encountered in translating legal texts and consequences of such errors in professional translation. First of all, the paper points out the importance of performing a good and correct translation, which is one of the most important elements to be considered when discussing translation. Furthermore, the paper presents an overview of the errors and difficulties in translating texts and of the consequences of errors in professional translation, with applications to the field of law. The paper is also an approach to the differences between languages (English and Romanian) that can hinder comprehension for those who have embarked upon the difficult task of translation. The research method that I have used to achieve the objectives of the paper was the content analysis of various Romanian and foreign authors' works.